Impaired circadian rhythm of blood pressure predicting adverse events in preeclampsia - Vijayvargia, Nitisha; Samariya, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Physiologically Blood pressure is higher during the day time (between 09 AM to 6 PM) and lower at night (10 pm to 3:00 am). During night both systolic and diastolic blood pressure readings drop by about 10-20%. In preeclampsia, the nocturnal decrease of BP is blunted and there is less variation among BP circadian values. Objective of the study is to know whether ratio of morning and nocturnal mean diastolic blood pressures calculated by timed i.e., 6 hourly blood pressure monitoring could be used to predict the prognosis of preeclampsia as in terms of Maternal and fetal prognosis. Methods: A prospective study is done using 6 hourly blood pressure measurements of antenatal patients in third trimester admitted for gestational hypertension or preeclampsia and their observation till delivery was done. Results: It is observed that non dipping and increased nocturnal diastolic blood pressures pattern causing reverse dipping pattern are significantly associated with increased severity of disease (p=000). Both maternal (p=0.04) and fetal adverse event (p=0.004) increased significantly with blunting of decrease in nocturnal blood pressures. Conclusions: We thus can conclude that blunting/reversal of circadian rhythm of blood pressure indicates progress of disease to its more severe form. It thus could be of great help in deciding for monitoring, timing of antihypertensives and prophylactic medications and deciding for termination of gestation.